Neurotrophin Signaling Is Required for Glucose-Induced Insulin Secretion. - Houtz, J; Borden, P; Ceasrine, A; Minichiello, L; Kuruvilla, R (Cell Press, 2016)
Insulin secretion by pancreatic islet β cells is critical for glucose homeostasis, and a blunted β cell secretory response is an early deficit in type 2 diabetes. Here, we uncover a regulatory mechanism by which glucose recruits vascular-derived neurotrophins to control insulin secretion. Nerve growth factor (NGF), a classical trophic factor for nerve cells, is expressed in pancreatic vasculature while its TrkA receptor is localized to islet β cells. High glucose rapidly enhances NGF secretion and increases TrkA phosphorylation in mouse and human islets. Tissue-specific deletion of NGF or TrkA, or acute disruption of TrkA signaling, impairs glucose tolerance and insulin secretion in mice. We show that internalized TrkA receptors promote insulin granule exocytosis via F-actin reorganization. Furthermore, NGF treatment augments glucose-induced insulin secretion in human islets. These findings reveal a non-neuronal role for neurotrophins and identify a new regulatory pathway in insulin secretion that can be targeted to ameliorate β cell dysfunction.